Semiotics label in the Dalia Duaeed Bin al- summa - اخلاص محمد عيدان (College of Education for Women, 2019)
Form naming system Simiaúaa can not be studied in isolation from the dimensionality of social and psychological , no doubt that names carry data psyche during social interaction , deflagration volunteered her body signifier in formats that meet the margin emotional part of the signified , Vtngams forms functions in coordinated trading to function as semantic double , it operates on coding , as well as carry emotional charge . The science of semiotics cares Pettmvsal indications and forms of circulation, and is made form the semantic patterns , and pattern of production , and methods of functioning . Stop quite a few specialists and critics and researchers at Dalia ignorant poet and knight known ( Duraid bin embolism Jashmi ) ; it represents a turning point of views setting their sights on the poems of lamentation ignorance stereotypes , and after the study and scrutiny and audit in the poem and found that most of the opinions of those who ate research and analysis did not come to fruition because they had made the turnaround or rags in the pattern eulogy directed away caught in the so- display historian Arabic around, and it was for the label impact sole decode and talismans surrounding Dalia Duraid this by offering these names and Astjlat assets and realities until I got out of the poem after reading semiotic Modern System new unexpected , as it was necessary to accompany the pattern within the deliberative semiotic approach to realizing the offsets in stylistic reasons, the label in this poem within the system of the common language , and to understand the goals or targets from behind .